Characterization of the rat neutral and basic amino acid transporter utilizing anti-peptide antibodies. - Mosckovitz, R (1993)
High-titer, site-specific antibodies have been produced against the rat kidney broad-spectrum, sodium-independent neutral and basic amino acid transporter (NBAA-Tr) whose cDNA we cloned earlier. These antibodies have allowed us to characterize the transporter protein in normal rat tissues and in various cellular and in vitro expression systems. Western analysis detected 84- to 87-kDa glycosylated species enriched in rat renal and jejunal epithelial cell brush border membranes. In vitro translation of NBAA-Tr complementary RNA in the rabbit reticulocyte lysate system yielded a 78-kDa protein, a molecular mass that was predicted by the amino acid sequence deduced from the cloned cDNA. Translation in the presence of rough microsomal membranes yielded a glycosylated 89-kDa species. Glycosylated 87- to 89-kDa species were also expressed in Xenopus oocytes microinjected with NBAA-Tr complementary RNA and in COS-7 cells transfected with NBAA-Tr cDNA. Localization of NBAA-Tr in renal and intestinal brush border membranes is consistent with its proposed role in transepithelial transport of amino acids.